Self and trans identities: social contingencies and aversive control in the identity and experiences of binary transgenders - Zin, Gabriela de Oliveira; Gama, Viviane Dutra; Reis, Maria de Jesus Dutra dos (Perspectivas em Análise do Comportamento, 2022)
Transgender people are systematical targets of violence and rights violations. Gendered cultural practices directly influence on how society negatively respond to these people and the development of self of those that are not living accordingly the cis normative standards. Thus, the aim of this paper is to offer a contextual behavioral interpretation of the development of the transgender identities build in the notion of self. Also, we discuss the role of control agencies on the perpetuation of gendered practices and its relationship with transgender identities, especially the role of psychotherapy. We point out how trans identities are continuously invalidated and some possible outcomes and discuss culturally programmed contingencies that marginalize trans people with the goal to perpetuate social control through gender. Ultimately, we argue that functional analysis is one of the main tools within behavioral therapies for affirmative care of transgender people.